ANALISIS LOYALITAS KONSUMEN BUNGA POTONG BERDASARKAN KUALITAS PRODUK DAN KEPUASAN KONSU - Pujihastuti, Isti (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2012)
There are increasing demand to cut flowers. Are there any customer’s loyalty? Loyalty is one attractive concept to be understand for business survival. The first aim of the research is to description about cut flowers consumer’s loyalty. And the second is to prove that product quality and customer’s satisfaction are influence to cut flowers customer’s loyalty. A lot of indicator that influence to customer’s loyalty but this research is restricted to two variables only. Validity and reliability test were done for 30 responden and the result show that the instrument were valid and reliable. By convenience sampling, the research instrument that are questionairs was distributed to 100 respondens. Research has shown that two variables were statistic significantly influence to customer’s loyalty. This result based on regression analysis. Product quality and customer’s satisfaction are partially and simultaneous influence to customer’s loyalty. So to increase the customer’s loyalty,which is the main target of current marketing, the business institution need to increase the quality product and or the customer’s satisfaction. Descriptionally, there are three indicator that is lower performance: the first is demonstrater an immunity to the full of the competion; the second is durability of product; the third is the wants and the needs of customer’s satisfaction namely product price of cut flowers.